Isolation of an ampicillin-resistant, non-beta-lactamase-producing strain of Haemophilus influenzae. - Markowitz, S M (1980)
A 79-year-old female developed endocarditis and meningitis due to an ampicillin-resistant, non-beta-lactamase-producing strain of Haemophilus influenzae. Carbenicillin and gentamicin therapy resulted in bacteriological and clinical cure. The mechanism of resistance of ampicillin-resistant, non-beta-lactamase-producing strains of H. influenzae is unknown.